Optimization of Flood Dispatch Scheme in Upstream of Beijiang River Based on Traceability Analysis - QIN Yehongping; LI Ningning; TAN Chao; LIU Zhimin; XU Jingfeng (Renmin Zhujiang)
In order to deeply understand the new situation and demand for flood control in the upstream of Beijiang River and ensure the safety of key flood control and protection objects in the upstream, the Pearl River Delta in the downstream, and the Guangdong-Hong Kong-Macao Greater Bay Area, research was conducted on the practical dispatch results of the "22·6" and "24·4" Beijiang major floods. Based on the traceability analysis method, the factors that limit the flood control capacity of the Wantou Reservoir were clarified, and practical experience was summarized. On this basis, the potential of flood control and peak shifting of the Lechangxia Reservoir was fully explored, and an optimized dispatch scheme for the Lechangxia Reservoir was proposed. The Jinjiang Reservoir was considered to be included in the joint dispatch. Finally, multidimensional flood control benefit risk indicators were used to evaluate the optimization schemes. The research results indicate that when the inflow of the Wantou Reservoir exceeds 5 300 m3/s, holding back the water and storing it up in the Lechangxia Reservoir in advance can effectively reduce the maximum water level of the Wantou Reservoir by 1.75–3.53 m and alleviate the flood control pressure of the Wantou Reservoir. Including the Jinjiang Reservoir in the joint dispatch can further reduce the peak flow of the Shaoguan by 25–89 m3/s. The research results aim to provide a reference for optimizing flood dispatch schemes and arranging flood discharge routes in the upstream of Beijiang River under new engineering and social conditions.